Structural evolution in 146–158 Nd isotopes using IBM-2 Hamiltonian - Nasef, Dalenda; Eshaftri, Najat S. Eshaftri; Ezwam, Ayad Ezwam; Bogrin, Suad M. Bogrin; Elbendag, Asma A. Elbendag; El-kadia, Sadiq M. El-kadi (Journal of Pure & Applied Sciences, 2021)
Neodymium isotopes (Z=60) lie in the traditional rotational to transitional-spherical region that occurs at the range of deformed nuclei. The identity of 146−158 Neodymium nuclei have been determined in framework of Interacting Boson Model-2, a simulation program with NPBOS has been built to obtain the theoretical energy levels for Neodymium isotopes. The parameters of the best fit to the measured data are determined. The energy positive parity bands of those isotopes were calculated using (IBM-2) and then it compared with the experimental values. The mentioned isotopes ratios have calculated and also E-GOS curves ) have drawn as a function of the spin I, to classify symmetry of the nuclei. The electromagnetic transition probabilities B(E2) of these nuclei was calculated as well, where a good agreement for low lying energy states were obtained between experimental results and theoretical calculations. The results have been shown that the interested nuclei 152-158Nd have rotational characters SU (3), and O (6) symmetry is substantiated for 146-148Nd, as well as the critical point X (5) has been determined for 150Nd isotope.